Three-dimensional Electrocoagulation Process Optimization Employing Response Surface Methodology that Operated at Batch Recirculation Mode for Treatment Refinery Wastewaters - Theydan, Samar K.; Mohammed, Wadood T.; Haque, SK Manirul (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
The performance of a three-dimensional electrocoagulation process operated at a batch recirculation mode for treating petroleum refinery wastewater using aluminium as a sacrificial anode, stainless steel as a cathode, and granular activated carbon with metal impregnated carbon (GACMI (Al: Fe)) with mass ratio (2:1) as a third particle electrode was investigated. Effects of operating factors such as the applied voltage (15-30 v), flow rate (50-175 mL/min), pH (4-10), and GACMI dosage (5-10) g/L on the chemical oxygen demand removal were investigated. Using Box-Behnken design (BBD), a mathematical model relating the essential operational parameters to chemical oxygen demand (COD) reduction was constructed. Results showed that the effect of GACMI dosage on the efficiency of COD removal was the major one, where COD removal increased as GACMI dosage increased. However, increasing applied voltage would enhance the performance of the electrocoagulation reaction. Experimental chemical oxygen demand removal of 96.25 % was attained at the optimized conditions (applied voltage=27.7 v, flow rate=128 mL/min, pH=5.6, GACMI dosage= 8.7 g/L). BET-specific surface area, total pore volume, X-ray fluorescence (XRF), energy-dispersive X-ray spectroscopy (EDX), and scanning electron microscopy (SEM) were employed for the characterization of GACMI particle electrodes.